Molecular diagnosis and genotype analysis of Giardia duodenalis in asymptomatic children from a rural area in central Colombia (2015)
Giardiasis is a parasitic infection that affects around 200 million people worldwide. This parasite presents a remarkable genetic variability observed in 8 genetic clusters named as 'assemblages' (A-H). These assemblages are host restricted and could be zoonotic where A and B infect humans and animals around the globe. The knowledge of the molecular epidemiology of human giardiasis in South-America is scarce and also the usefulness of PCR to detect this pathogen in fecal samples remains controversial. The aim of this study was to conduct a cross-sectional study to compare the molecular targets employed for the molecular diagnosis of Giardia DNA and to discriminate the parasite assemblages circulating in the studied population. We analyzed 181 fecal samples from Children at La Virgen, Cundinamarca, Colombia that were DNA-extracted and analyzed by SSU rDNA, tpi and gdh loci. We observed positivity by microscopy of 13% and by PCR around 76-80% depending on the molecular marker. Additionally, a lack of statistical concordance between microscopy and PCR was detected. Regarding the genetic assemblages, we detected assemblage A (3%), assemblage B (90%) and mixed infections assemblages A. +. B (7%). Hence, the sub-assemblages were typed as AI, AII, BIII and BIV across the population. This study represents a reliable attempt to understand the molecular epidemiology of giardiasis in Colombia and the use of PCR to detect cryptic infections. The epidemiological implications are herein discussed. © 2015 Elsevier B.V.